A room temperature volatile organic compound sensor with enhanced performance, fast response and recovery based on N-doped graphene quantum dots and poly(3, 4-ethylenedioxythiophene)–poly(styrenesulfonate) nanocomposite. Issue 71 (2nd August 2015) - Gavgani, Jaber Nasrollah; Dehsari, Hamed Sharifi; Hasani, Amirhossein; Mahyari, Mojtaba; Shalamzari, Elham Khodabakhshi; Salehi, Alireza; Taromi, Farmarz Afshar
<x xml:space="preserve">Abstract</x> A highly efficient VOC sensor based on N-doped graphene quantum dots (N-GQDs)/poly(3, 4-ethylenedioxythiophene)–poly(styrenesulfonate) (PEDOT–PSS) was fabricated at room temperature.